Suicide attempt and its associated factors amongst women who were pregnant as adolescents in Bangladesh: a cross-sectional study - Jie Li; Syeda Zerin Imam; Zhengyue Jing; Yi Wang; Chengchao Zhou (BMC, 2021)
Abstract Background Adolescent pregnancy is a risk factor for suicide. We aimed to assess the prevalence of suicide attempts among young women with adolescent pregnancy in Bangladesh and to explore its associated factors. Methods In this cross-sectional study, we surveyed young women with adolescent pregnancy in urban and rural areas in Bangladesh to assess suicide attempts, socio-demographic and pregnancy-related characteristics, perceived health status, and perceived social support. Binary logistic regression analysis was conducted to explore the relationship between potentially related factors and suicide attempts. Results Of the participants, 6.5% (61/940) reported suicide attempts in the past 12 months, and the majority (88.5%) of the attempts happened within one year after the pregnancy. Participants with more years after first pregnancy (odds ratio (OR) = 0.47, 95% CI: 0.37-0.61) and more perceived social support from friends (OR = 0.69, 95% CI: 0.55-0.86) were less likely to have suicide attempts, and those perceived bad health status compared with good/fair health status (OR = 8.38, 95% CI: 3.08-22.76) were more likely to attempt suicide. Conclusions Women with adolescent pregnancy were at high risk of suicide attempts, especially those during the first postnatal year. The risk of suicide attempts attenuated with the time after pregnancy, and perceived social support from friends was a protective factor and perceived bad health status was a risk factor for suicide attempts among young women who have experienced adolescent pregnancy.